ERASE-ing Patient Mistreatment of Trainees: Faculty Workshop - Kirsten M. Wilkins; Matthew N. Goldenberg; Kali D. Cyrus (Association of American Medical Colleges, 2019)
Introduction Mistreatment of physicians by patients is a long-standing phenomenon that has garnered increased attention recently. Medical students and residents also experience mistreatment, and many supervising physicians do not know how to recognize it or respond appropriately. Little guidance exists as to how faculty should best address these situations. We developed, taught, and evaluated a stepwise approach to help faculty physicians manage patient mistreatment of trainees (residents and students). Methods Our approach is summarized by the acronym ERASE: (1) Expect that mistreatment will occur. (2) Recognize episodes of mistreatment. (3) Address the situation in real time. (4) Support the learner after the event. (5) Establish/encourage a positive culture. We designed an interactive, case-based educator development session to teach ERASE and surveyed participants before and after to evaluate the session. Sixty-nine participants attended one of four workshops between November 2017 and January 2018. Results Nearly 80% of attendees reported having received no prior training in managing mistreatment of trainees by patients. Participants noted significant changes in their confidence in recognizing and responding to episodes of mistreatment after the session compared with just prior to it. Discussion ERASE fills an important void in medical education by introducing a novel, easy-to-understand approach that faculty can employ to manage mistreatment of trainees. We have continued to disseminate this model to faculty and residents in various departments around our medical center and at national conferences. This resource will allow educators to disseminate the ERASE model at their home institutions.